Microtopia land game board with AR - Shakeeb Arsalaan Bajunid, Siti Farhana Bajunid; Azman, Amira Fathini; Ramdzan, Amirul Idzham; Mohd Zainul Arifien, Ameerul Adib; Saad, Wan Zuhainis (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Gamification or game-based learning is for capturing learner’s imagination and creativities. The Microtopia Land Game Board brings learners to a journey to explore and learn about microbes in a very fun, interesting and imaginative way. A game board that provides learners the learning adventure they will never forget because learning is supposed to be fun.